Rehabilitation of Beam Column joint using Steel Fibrous Concrete - Anoop Kumar, A; Ranga Rao, V; Achyutha Reddy, M (International Journal of Engineering and Technology, 2018)
An experimental study was conducted to compare the structural behavior of beam column joint before and after rehabilitation by using fibrous concrete with steel fibers as a strength enhancer material. Two specimens were examined in this study out of which one was designed according to IS 456: 2000 (control specimen) codal provision and another one was designed according to IS 13920:2016(ductile specimen). Both the supports at top and bottom faces of the column were hinged, and the load was applied on the edge of the beam. TheÂ Â parameter observed during the experiment was Load- deflection response for both control and rehabilitation specimens. The ultimate load carrying capacity for rehabilitated controlled specimen increased by 36.6% in comparison with controlled specimen, and the ultimate load carrying capacity for rehabilitated ductile specimen increased by 62.3% in comparison with ductile specimen. It has been observed that steel fiber reinforced concrete can enhance flexural strength, ductility and crack arrest.Â Â